2014
DOI: 10.1044/2014_jslhr-s-13-0292
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Speech Intelligibility With a Multiple Speech Subsystems Approach in Children With Cerebral Palsy

Abstract: Purpose Speech acoustic characteristics of children with cerebral palsy (CP) were examined with a multiple speech subsystem approach; speech intelligibility was evaluated using a prediction model in which acoustic measures were selected to represent three speech subsystems. Method Nine acoustic variables reflecting different subsystems, and speech intelligibility, were measured in 22 children with CP. These children included 13 with a clinical diagnosis of dysarthria (SMI), and nine judged to be free of dysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
106
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 66 publications
(92 reference statements)
11
106
4
4
Order By: Relevance
“…Reduced vowel space area in adults with dysarthria has been found in single-word contexts (Liu et al, 2005), as well as in connected speech (Tjaden, Lam, & Wilding, 2013;Turner et al, 1995;Weismer et al, 2001). Studies of children have consistently found that reduced vowel space area is associated with dysarthria and correlated with reduced intelligiblity in pediatric populations (Higgins & Hodge, 2002;Hustad et al, 2010;J. Lee et al, 2014); however, to date, studies of vowel space area in children with CP have exclusively examined single-word productions, and it is currently unknown whether findings indicating reduced vowel space area also apply to connected speech.…”
Section: Acoustic Indicators Of Articulatory Imprecisionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reduced vowel space area in adults with dysarthria has been found in single-word contexts (Liu et al, 2005), as well as in connected speech (Tjaden, Lam, & Wilding, 2013;Turner et al, 1995;Weismer et al, 2001). Studies of children have consistently found that reduced vowel space area is associated with dysarthria and correlated with reduced intelligiblity in pediatric populations (Higgins & Hodge, 2002;Hustad et al, 2010;J. Lee et al, 2014); however, to date, studies of vowel space area in children with CP have exclusively examined single-word productions, and it is currently unknown whether findings indicating reduced vowel space area also apply to connected speech.…”
Section: Acoustic Indicators Of Articulatory Imprecisionmentioning
confidence: 99%
“…For children with cerebral palsy (CP), articulatory imprecision is a common perceptual feature of dysarthria (Hustad, Gorton, & Lee, 2010;Nip, 2013Nip, , 2017Workinger & Kent, 1991). Prior research has identified acoustic correlates of reduced intelligibility in children with CP (Higgins & Hodge, 2002;Hsu, Chen, & Cheng, 2013;Hustad et al, 2010;J. Lee et al, 2014); however, little is known empirically about the movement characteristics underlying this imprecision in children with CP.…”
Section: Range and Precision Of Formant Movement In Pediatric Dysarthriamentioning
confidence: 99%
See 3 more Smart Citations